PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH SEKOLAH TINGGI ILMU EKONOMI (STIE) NGANJUK - Mahardhika, Mustafidah (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
The aim of this research is to find out the effect of marketing mix strategy influence college student’s decision to choose Institute of Nganjuk Economic Science. To achieve the goals of this research, researcher uses quantitative research approach with survey research method. Variables in this research are the component of 4P’s marketing mix, consisting of product, price, promotion, and place. Based on data analysis uses multiple linierity regression analyze, we can conclude that marketing mix strategy has simultaneous influence toward college student’s decision to choose Institute of Nganjuk Economic Science. Partially, variable of product, price, promotion, and place are influence significantly university student’s decision to choose Institute of Nganjuk Economic Science. All those variables have 87,7 % contribution to influence university student’s decision to choose Institute of Nganjuk Economic Science.